Radiolarians decreased silicification as an evolutionary response to reduced Cenozoic ocean silica availability - Kotrc, Benjamin; Wulf, Gerwin; Schmidt, Daniela N.; Lazarus, David (Proceedings of the National Academy of Sciences, 2009)
It has been hypothesized that increased water column stratification has been an abiotic “universal driver” affecting average cell size in Cenozoic marine plankton. Gradually decreasing Cenozoic radiolarian shell weight, by contrast, suggests that competition for dissolved silica, a shared nutrient, resulted in biologic coevolution between radiolaria and marine diatoms, which expanded dramatically in the Cenozoic. We present data on the 2 components of shell weight change—size and silicification—of Cenozoic radiolarians. In low latitudes, increasing Cenozoic export of silica to deep waters by diatoms and decreasing nutrient upwelling from increased water column stratification have created modern silica-poor surface waters. Here, radiolarian silicification decreases significantly (r = 0.91, P < 0.001), from ≈0.18 (shell volume fraction) in the basal Cenozoic to modern values of ≈0.06. A third of the total change occurred rapidly at 35 Ma, in correlation to major increases in water column stratification and abundance of diatoms. In high southern latitudes, Southern Ocean circulation, present since the late Eocene, maintains significant surface water silica availability. Here, radiolarian silicification decreased insignificantly (r = 0.58, P = 0.1), from ≈0.13 at 35 Ma to 0.11 today. Trends in shell size in both time series are statistically insignificant and are not correlated with each other. We conclude that there is no universal driver changing cell size in Cenozoic marine plankton. Furthermore, biologic and physical factors have, in concert, by reducing silica availability in surface waters, forced macroevolutionary changes in Cenozoic low-latitude radiolarians.